Analysis of Relationship between Work Attitudes and Repetitive Activities with Subjective Complaints on Musculoskeletal Disorder in Circular Loom Division workers PT. Kerta Rajasa Raya Sidoarjo Indonesia - Yuly Eka Saputri1, Y. Denny Ardyanto W2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The Musculoskeletal System Disorders (MSDs) are one of the most common occupational diseasesexperienced by workers. This disorder is influenced by several factors, such asrepetitive activity factor andunnatural work attitude factor. The purpose of this study was to analyze the strong relationship betweenwork attitude and repetitive activity with subjective complaints of musculoskeletal disorder in the circularloom division of PT. Kerta Rajasa Raya Sidoarjo, Indonesia.This study used observational techniques with cross-sectional design. Respondents in this study wereworkers in the circular loom division of PT. Kerta Rajasa Raya, Sidoarjo, that consisted of 14 peoplebased on the researchers’ inclusion criteria. The data were obtained from the results of questionnaires andfield observations. Work attitude data were analyzed using OWAS; MSDs subjective complaint data wereinvestigated using NBM checklist sheets; and repetitive activity data were analyzed based on the results ofquestionnaires, interviews, and observations.The results showed that the majority of respondents have subjective complaints of musculoskeletal disorderwith high severity. The work attitude variable has a very strong correlation with subjective complaints ofMSDs, and repetitive activity variable has a strong correlation with subjective complaints of MSDs.The company are advised to provide training related to safe lifting method, provide information related toMSDs in the form of posters or providing specific material. Companies are also advised to add the expeditionpersonnel to reduce the repetition of lifting activities.